A profiling acoustic and optical system (pAOS) for pelagic studies; Prototype development and testing - Marouchos, A.; Sherlock, M.; Kloser, Rudy; Ryan, T.; Cordell, J. (2016)
© 2016 IEEE.In support of ecosystem and fisheries studies, the CSIRO has developed and deployed a variety of towed and tethered acoustic and optical systems to quantify fish biomass and characterize the ecosystem. The most recent of these platforms - the acoustic and optical system (AOS) - was designed to provide both acoustic and imaging data for fisheries studies. When vertically deployed the AOS can provide fine scale concurrent acoustic and optical measurements to obtain detailed profiles that enable characterization of the water column biota. The instruments were lowered via a steel cable, coupling it directly to the vessel's heave effects at the surface. These heave effects were observed directly in the acoustic and optical data with the range to the biological targets constantly varying and their behavior. Decoupling the deployed instrument from the support vessel was a vital step to improve data quality and science outcomes. A self-contained profiling acoustic and optical system (pAOS) was envisioned that would combine the sensor payload from the AOS platform, with the ability to conduct self-contained, untethered profiles in open water. In order to evaluate the feasibility of this concept, a prototype pAOS system was developed and extensively tested. This paper will discuss the design, development and testing of the prototype profiling acoustic and optical system for pelagic ecosystem studies. The design challenges are presented along with a discussion of difficulties in the operation of this system at sea. Finally the paper discusses next phases of development the system leading to a more fully autonomous pAOS platform.